DRIFT and Theoretical Studies of Ethylene/Ethane Separation on Flexible and Microporous [Cu2(2, 3‐pyrazinedicarboxylate)2(pyrazine)]n (Eur. J. Inorg. Chem. 17/2014). Issue 17 (June 2014) - Kishida, Keisuke; Watanabe, Yumiko; Horike, Satoshi; Watanabe, Yoshihiro; Okumura, Yoshikuni; Hijikata, Yuh; Sakaki, Shigeyoshi; Kitagawa, Susumu
Abstract : The cover picture shows the adsorption‐based separation of ethylene from ethane by [Cu2 (2, 3‐pyrazinedicarboxylate)2 (pyrazine)] n (CPL‐1), which was investigated with both single and binary gas systems. The separation originates from the difference in the hydrogen bonding between CPL‐1 and C2 hydrocarbons, which were confirmed by spectroscopic and computational methods. The background is a view of the Oita chemical complex where cryogenic distillation of ethylene is conducted every day. The members of our research team from Showa Denko work at a laboratory located at this complex. Details are discussed in the article by S. Kitagawa et al. onp. 2747 ff . For more on the story behind the cover research, see theCover Profile .